Group Activity Therapy as an Effort to Prevent Elderly Frailty in Panti Sosial Tresna Werdha Bengkulu City - Titin Aprilatutini; Nova Yustisia; Maiyulis Maiyulis (CV Media Inti Teknologi, 2022)
The targets of this community service activity are:community, especially the elderly.The location for the activity was held at the Panti Sosial Tresna Werda (PSTW) Bengkulu City. PSTW is a residential institution that provides physical, spiritual and social services and care as well as protection for the elderly so that they can enjoy old age like other elderly people. Group activity therapy as an effort to prevent frailty in the elderly has many benefits as one of the most effective interventions to be used in medical therapy for healing a disease that can be applied to the community as therapy, one of which is in the elderly so that the elderly avoid frailty which will affect the elderly. quality of life of the elderly.The hope is that after this activity is carried outcan help social workers and health workers who are in PSTW to improve the welfare of the elderly and prevent the occurrence of frailty in the elderly so that their functional health can be maintained and improve the quality of life of the elderly.